2023
DOI: 10.3389/fvets.2023.1161935
|View full text |Cite
|
Sign up to set email alerts
|

“Dying alone and being eaten”: dog scavenging on the remains of an elderly animal hoarder-a case report

Louise Bach Kmetiuk,
Paulo César Maiorka,
Alan M. Beck
et al.

Abstract: Animal hoarding and human consumption by dogs have been important but often understudied aspects of the human-animal bond that can be addressed within a One Health framework. No scientific report has focused on dog scavenging on animal hoarders to date, despite isolated reports of dog scavenging on human remains, mostly due to starvation. The phenomenon has been approached as a confounding factor for human forensics. In 2014, the Animal Protection Department of Curitiba City was called to rescue and handle ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Hoarding disorder cases are challenging mostly due to neglect, the multiplicity and complexity of associated factors [5], and difficulty accessing affected populations [7]. A recent study in the Metropolitan Region of Curitiba, Parana ´, indicated challenges faced by the City Hall official services regarding animal hoarding disorders, such as the lack of standardization and exchange of service information between the involved city secretaries, including health, environment, and social services [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hoarding disorder cases are challenging mostly due to neglect, the multiplicity and complexity of associated factors [5], and difficulty accessing affected populations [7]. A recent study in the Metropolitan Region of Curitiba, Parana ´, indicated challenges faced by the City Hall official services regarding animal hoarding disorders, such as the lack of standardization and exchange of service information between the involved city secretaries, including health, environment, and social services [50].…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with AHD often live in unsanitary conditions, leading to vector proliferation and pathogen spread, particularly of zoonotic diseases [1,[3][4][5][6]. In addition, such individuals often fail to recognize animal suffering, are often hungry, trapped, crowded, or even die [1], as indicated by case reports of dogs scavenging the owner's remains [7].…”
Section: Introductionmentioning
confidence: 99%